PERANCANGAN PEMBUATAN APLIKASI PENJUALAN TIKET BERBASIS DESKTOP PADA FAMILY TOUR & TRAVEL MENGGUNAKAN VISUAL BASIC .NET - Hendri Hendri; Desi Arisandi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
The sales process and recording of transaction data in the CV Family Tour & Travel is still done manually, so often found errors in recording transaction data and preparing the report. The problems that arise in CV Family Tour & Travel behind the construction of a system that can help in overcoming the problems that exist today. Then designed a system of ticket sales information using Microsoft Visual Studio 2012 and SQL Server Management Studio 2012-based desktop with SDLC development method is expected to help the processing of the transaction process and preparing reports on the CV Family Tour & Travel. The function of the application program for the sale of tickets, print E-Ticket, transaction point member (with redeem point), the financial statements: Details, Transportation and Annual. Tests performed on CV Family Tour & Travel where the test results were possesing some problems and issues that still need to be improved as the data on the member can’t be replaced, all the member data erased with one click without confirmation, can’t perform data input ticket number with character, and others. Results of testing the application program CV Family Tour & Travel has been repaired and running well and smoothly without any obstacles or problems in the program.